Mindful Parenting and Emotion Regulation in Early Childhood: A Relational Process Perspective from a Systematic Review - Al Adawiyah, Robiah; Mustapa, Noviana; Tatminingsih, Sri; Maryatun, Ika Budi; Himphinit, Musakkid (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
Research on mindful parenting, caregiver emotion regulation, and children’s emotion regulation has expanded, yet the literature remains fragmented, especially in early childhood and across non-Western settings. Many studies treat these constructs as separate variables and therefore provide limited clarity on how they are linked within everyday caregiving relationships. This systematic literature review examined how mindful parenting, maternal emotion regulation, and children’s emotion regulation have been connected in recent scholarship on early childhood caregiving. Guided by PRISMA 2020, the review searched Scopus, ScienceDirect, Wiley Online Library, and Frontiers in Psychology for studies published between 2019 and 2024. Ten eligible studies were included and interpreted through narrative thematic synthesis. The findings suggest that mindful parenting is more convincingly understood as a relational orientation shaping the emotional climate of caregiving than as a discrete technique. Maternal emotion regulation emerges as an interactional mechanism operating through modeling, responsiveness, emotion socialization, and co-regulation, while children’s regulatory development appears within broader systems of attachment, executive functioning, and socio-emotional competence. The evidence, however, remains uneven. Variability in study design, modest effect sizes, reliance on cross-sectional and self-report data, and the continued dominance of Western samples indicate that these pathways are context-sensitive rather than universally causal. This review advances a relational process perspective that refines family-based models of emotion regulation and contributes to global debates on parenting and child development by showing why culturally responsive interpretations are necessary when translating evidence across diverse caregiving contexts.